Validity of Non Disclosure Agreement as The Protection Undisclosed Information : (Trade Secret in Indonesia) - Suriyadi, Suriyadi; Nur, Muhammad Azhar (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2025)
Undisclosed information that has economic value and is not published is an intellectual work that is recognized and protected as intellectual property rights. Business actors and owners of confidential information use various means to protect this information, although basically the law has regulated this through Law Number 30 of 2000, one of which is a non-disclosure agreement or confidentiality agreement were used to protect undisclosed information beside the Indonesian Law. The research method used in this study is normative legal research with two approaches (conceptual approach and statute approach). A non-disclosure agreement as an agreement is made to bind the parties to protect confidential information both during the work/business relationship and after the relationship ends. The binding power of the NDA applies like a law based on the principle of pacta sunt servanda and it is the obligation of the parties to comply with the agreement based on the principle of good faith. NDA legal instruments are the scope of civil law so that the output is in the form of lawsuits for violations to restore rights or demand compensation. Besides that, there is an option of criminal enforcement for violations of trade secrets in the Trade Secret Law.